1992
DOI: 10.1071/bt9920445
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Elevated Atmospheric CO2 Concentrations on Plant Nutrition

Abstract: The rising levels of atmospheric CO2 are likely to increase biomass production of C3 species in both natural and managed ecosystems because photosynthetic rates will be higher. The greatest absolute increase in productivity will occur when nitrogen and phosphorus availability in the soil is high. Low nitrogen does not preclude a growth response to high CO2, whereas some C3 species fail to respond to high CO2 when phosphorus is low, possibly because insufficient phosphorus is available to maintain maximum phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
129
4
3

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(143 citation statements)
references
References 0 publications
7
129
4
3
Order By: Relevance
“…Reduction in nutrient concentration of plants due to increased [CO 2 ] concentration has been reported by earlier studies [10]- [12]. The reason attributed to the uptake of nutrient from the soil is not increased in relation to the increased net carbon assimilation may leading to changes in the nutritional quality of the crops.…”
Section: Effect Of Elevated Co 2 and Soil Moisture On Leaf Carbon Andmentioning
confidence: 73%
See 2 more Smart Citations
“…Reduction in nutrient concentration of plants due to increased [CO 2 ] concentration has been reported by earlier studies [10]- [12]. The reason attributed to the uptake of nutrient from the soil is not increased in relation to the increased net carbon assimilation may leading to changes in the nutritional quality of the crops.…”
Section: Effect Of Elevated Co 2 and Soil Moisture On Leaf Carbon Andmentioning
confidence: 73%
“…Previous studies also reported reduction in leaf nitrogen concentration with elevated [CO 2 ] in different crop species [12]- [14] [82]. This reduction in nitrogen may be either due to the dilution effect as a result of greater carbohydrate accumulation [13] or due to the acceleration of plant growth, but not due to the increased nitrogen use efficiency [83].…”
Section: Effect Of Elevated Co 2 and Soil Moisture On Leaf Carbon Andmentioning
confidence: 97%
See 1 more Smart Citation
“…The second potential indirect response to growth under high CO, concentration is a change in the relative distribution of N between the photosynthetic machinery as a whole and sinks and/or into the systems for acquiring other resources such as roots for mineral nutrient acquisition. This is suggested by the observation (Conroy, 1992) that plants from high CO, conditions always have a lower foliar Iq concentration than control plants, even when grown with abundant N supply. This was also true when foliar N concentration was expressed on a structural (rather than total) leaf dry weight basis (Rogers et al, 1993).…”
Section: Discussionmentioning
confidence: 89%
“…Thus, it might be hypothesized that increasing atmospheric CO 2 concentration favours osmotic adjustment through enhanced carbon supply to the different plant components and increased organic solute concentrations. However, elevated CO 2 concentrations often lead to reduced total mineral ion concentrations in the plant tissues (Conroy, 1992;Overdieck, 1993 Biomass partitioning between the plant compartments was assessed by determining i) the leaf mass ratio (LMR, leaf dry mass/whole plant dry mass, g g -1 ), ii) the stem mass ratio (SMR, stem dry mass/whole plant dry mass, g g -1 ), iii) the root mass ratio (RMR, root mass/whole plant mass, g g -1 ) and iv) the root:shoot ratio (root mass/[leaf mass + stem mass]). Specific leaf mass ratio (SLA, dm 2 g -1 ) and leaf area ratio (LAR, dm 2 g -1 ) were calculated as the leaf area to leaf mass and the leaf area to plant mass, respectively.…”
mentioning
confidence: 99%